Analysis of Internet Financial Reporting on The Financial Statements Of State-Owned Enterprises In Indonesia - Laely Aghe Africa; Mustika Dewi (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: This study aims to describe the presentation of SOEs’ financial information by presenting the Internet Financial Reporting (IFR) index. This study uses secondary data taken from the website of each SOE. This study uses a sample of all SOEs in Indonesia. The rapid development of the internet has significantly affected activities in the government, business and community, sectors. The internet has several characteristics and advantages in the overall disclosure of information, such as pervasiveness, unlimited access, timely communication, and low cost. Internet Financial Reporting (IFR) is a voluntary disclosure of financial statements through a company’s official website, in which its quality is measured using the IFR index. Law No. 14 of 2008 states that one important element regarding information disclosure is the public interest that affects the lives of many people. With this law, public companies, including State-Owned Enterprises (SOEs), must report all information related to their businesses through their websites Design/methodology/approach: The research method used is purposive sampling method with 2 observations, in November and December 2018. This study is classified as a quantitative study Findings: The results of this study indicate that there are still many SOEs that have not utilized the content, timeliness, technology used, and user support on their websites properly. Research limitations/implications: There is one sector that does not have a website, namely the sector of accommodation and food and drink providers. Practical implications: State your implication here. Originality/value: originality Paper type: Research paper